Successful treatment with transjugular intrahepatic portosystemic shunt (TIPS) of recurrent massive rectal bleeding due to portal hypertension: Case report - Yakup YEŞİLKAYA,; Barbaros ÇİL,; Bora PEYNİRCİOĞLU,; Halis Şimşek, (Turkish Journal of Gastroenterology, 2019)
-